2019
DOI: 10.1080/20430795.2019.1608709
|View full text |Cite
|
Sign up to set email alerts
|

Value matters or values matter? An analysis of heterogeneity in preferences for sustainable investments

Abstract: Pension fund investments have a substantial influence on sustainability. We analyze preferences for sustainable investment among a representative cross-section of 2486 pension fund participants in the Netherlands, through a questionnaire survey fielded in the LISS panel. In contrast to standard investment theory, we find that sustainable investments are commonly favored, even if they harm financial interests. To explain variation among participants' preferences for sustainable investments, we test socio-demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…The existence of dependants, related to the size of the family unit, was not statistically significant in Delsen and Lehr (2019) with regard to investors in pension funds in the Netherlands, and in Méndez-Rodríguez et al (2015), in relation to Spanish and Australian investors. However, Wins and Zwergel (2016) report a positive association between the existence of dependants and the probability that an individual will invest in socially responsible funds, whereas Rossi et al (2016) conclude that interest in financial products with SRI characteristics decreases if there are children in the household.…”
Section: Sociodemographic Factorsmentioning
confidence: 75%
See 4 more Smart Citations
“…The existence of dependants, related to the size of the family unit, was not statistically significant in Delsen and Lehr (2019) with regard to investors in pension funds in the Netherlands, and in Méndez-Rodríguez et al (2015), in relation to Spanish and Australian investors. However, Wins and Zwergel (2016) report a positive association between the existence of dependants and the probability that an individual will invest in socially responsible funds, whereas Rossi et al (2016) conclude that interest in financial products with SRI characteristics decreases if there are children in the household.…”
Section: Sociodemographic Factorsmentioning
confidence: 75%
“…The literature documents more homogeneous results for education. Chamorro-Mera and Palacios-González (2019), Delsen and Lehr (2019), Rossi et al (2019), Riedl and Smeets (2017), Wins andZwergel (2016), Pérez-Gladish et al (2012), Cheah et al (2011), Junkus and Berry (2010), Nilsson (2008), Haigh (2007), Getzner and Grabner-Kräuter (2004), Tippet (2001) and Woodward (2000) found a positive association between level of education, namely university education, and holding (or willingness to hold) SRIs, while Méndez-Rodríguez et al (2015) found the same association for Australia but not for Spain, and Williams (2007) and McLachan and Gardner (2004) did not find a statistically significant relationship between these variables.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 3 more Smart Citations